Terror the French Revolution and its demons - Biard, Michel 1957-; Linton, Marisa 1959- (Polity Press, 2021)
"A major new interpretation of the role of terror in the French Revolution"--
Keywords: Französische Revolution; Terreur; France / History / Reign of Terror, 1793-1794 / Psychological aspects; France / History / Reign of Terror, 1793-1794 / Historiography; France / History / Revolution, 1789-1799 / Psychological aspects; France / History / Revolution, 1789-1799 / Historiography; France / History / Revolution, 1789-1799 / Influence; Terror / France / History / 18th century; Terreur / France / Histoire / 18e siècle; Historiography; Influence (Literary, artistic, etc.); Psychological aspects; Terror; France; 1700-1799; History